Status quo of the rural zakat enterpreneurship development in Kuala Tahan, Pahang Malaysia: a way forward - Mohd Arif, Mohd Izzat Amsyar; Mat Rani, Mohd Afandi; Adenan, Faezy; Mama, Norazlina; Abbas, Mohd Saleh; Mat Naw, Rufaidah; Ismail, Albert Feisal @ Muhd Feisal (ResearchTrentz Academy Publishing Education Services, 2022)
One of the foundations that drives rural areas' economic growth is entrepreneurship initiatives. It is critical to satisfy society's requirements in terms of buying power, capacity to maintain life, and ability to endure in an ever-changing economic environment. As a result, the emphasis of this paper is on the application of rural entrepreneurship zakat as a strategy for improving the community's socioeconomic condition in Kuala Tahan, Pahang. The development of asnaf entrepreneurs in rural areas is discussed in this study. The goal of this research is to uncover government strategies for promoting rural asnaf entrepreneurs, as well as to examine the concerns, problems, and challenges faced by rural entrepreneurs. In developing a micro-entrepreneurship framework, this study employs both quantitative and qualitative research techniques. Focus group interview methods, either structured or semi-structured, were used to conduct the interviews, which included selecting a group of respondents with certain qualities to be questioned and preparing important questions. According to the results of this research, rural entrepreneur development initiatives get insufficient attention. Several suggestions have been made to support rural asnaf entrepreneurs so that they do not fall behind in national growth.